A Conceptual Framework for Optimizing Blood Matching Strategies: Balancing Patient Complications Against Total Costs Incurred - van Sambeeck, Joost H. J.; de Wit, Puck D.; Luken, Jessie; Veldhuisen, Barbera; van den Hurk, Katja; van Dongen, Anne; Koopman, Maria M. W.; van Kraaij, Marian G. J.; van der Schoot, C. Ellen; Schonewille, Henk; de Kort, Wim L. A. M.; Janssen, Mart P. (Frontiers in Medicine, 2018)
Alloimmunization is currently the most frequent adverse blood transfusion event. Whilst completely matched donor blood would nullify the alloimmunization risk, this is practically infeasible. Current matching strategies therefore aim at matching a limited number of blood groups only, and have evolved over time by systematically including matching strategies for those blood groups for which (serious) alloimmunization complications most frequently occurred. An optimal matching strategy for controlling the risk of alloimmunization however, would balance alloimmunization complications and costs within the entire blood supply chain, whilst fulfilling all practical requirements and limitations. In this article the outline of an integrated blood management model is described and various potential challenges and prospects foreseen with the development of such a model are discussed.